Türkiye Cumhuriyeti'nde ve Kuzey Kıbrıs Türk Cumhuriyeti'nde Akademik Personel Yapısı - Karadağ, Esma Nilsu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
This study aims to address the question „who constitutes the academic personnel working in the state and foundation universities in the Republic of Turkey‟ with a specific focus on the personnel‟s status, appointment procedures and working conditions, legal provisions, judiciary decisions and views of doctrines The current status of the academic personnel dealt with in this study has also been examined by taking into consideration all the differences resulting from working at the state and foundation universities. Afterwards, the academic personnel working at the universities in the Republic of Northern Cyprus have been evaluated in scope of Eastern Mediterranean University. Also, the relevant legislation of Higher education in Northern Cyprus and by-laws of Eastern Mediterranean University have been taken as basis during the analysis of the „said‟ subject. This study, limited by the working conditions of the academic personnel teaching at the universities in the Republic of Turkey and Northern Cyprus, has been carried out under three headings in line with the information obtained from various resources, namely legal provisions, judicial decisions, and doctrine views.

ÖZ: Bu çalıĢmada, Türkiye Cumhuriyeti Devlet üniversitelerinde ve Vakıf üniversitelerinde görev yapan akademik personelin kimlerden oluĢtuğu, statüleri, atama süreçleri ve çalıĢma koĢulları mevzuat hükümleri, yargı kararları ve doktrin görüĢleri çerçevesinde incelenmeye çalıĢılmıĢtır. Ġncelediğimiz akademik personelin mevcut durumu devlet ve vakıf üniversitelerinde görev yapmalarının getirdiği farklılıklar da göz önünde bulundurularak incelenmeye çalıĢılmıĢtır. Daha sonra Kuzey Kıbrıs Türk Cumhuriyeti üniversitelerinde görev yapan akademik personel mevzuat hükümleri çerçevesinde incelenmeye çalıĢılmıĢtır. Kuzey Kıbrıs Türk Cumhuriyeti'nde görev yapan akademik personel Doğu Akdeniz Üniversitesi örneği üzerinden değerlendirilmiĢ ve Kuzey Kıbrıs Türk Cumhuriyeti Yükseköğretim Yasası ve ilgili mevzuat ile birlikte Doğu Akdeniz Üniversitesi mevzuatları konunun incelenmesinde temel alınmıĢtır. Türkiye Cumhuriyeti ve Kuzey Kıbrıs Türk Cumhuriyeti üniversitelerinde görev yapan akademik personelin çalıĢma koĢulları ile sınırlı olan bu çalıĢma, mevzuat hükümleri, yargı kararları, doktrin görüĢleri gibi kaynaklardan elde edilen bilgiler neticesinde üç bölüm altında incelenmiĢtir.
Hukuk Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Hukuk Fakültesi, 2018. Tez Danışmanı: Prof. Dr. Levent Akın.
Keywords: Hukuk; Yükseköğretim--Üniversiteler--Akademik Personel--Hukuk--Türkiye--Kıbrıs; Akademik Personel; Üniversite; ÇalıĢma KoĢulları; Atama Süreci; Academic Personnel; University; Working Conditions; The Procedure Of Appointment